Accumulation of Microplastics in the Digestive Tract and Gonads and its Effects on Gonad Quality of Sea Urchins Tripneustes gratilla - Vanela Chatrin Lekatompessy; Agung Pramana Warih Marhendra; Nia Kurniawan (Biotropika: Journal of Tropical Biology, 2023)
Marine plastic debris will move with the flow of water and float and then be fragmented into smaller particles, namely microplastics, sink, and settle on the substrate. Sea urchins, as deposit feeders, can potentially ingest microplastic particles, which can influence changes in behaviour, growth, enzyme production, reproduction, and tissue structure. This study used a purposive sampling method with descriptive analysis for data related to the recording of morphometrics and gonadal quality, followed up with the Tukey and Pearson tests. This study aims to analyze how the accumulation of microplastics in the organs (digestive tract and gonads) affects the gonadal quality of sea urchins Tripneustes gratilla. The results show that the number of microplastic particles found in fi [1ve sea urchins from each beach was 233 particles/individual in the digestive tract of sea urchins and 205 particles/individual in the gonads with the colour variants transparent, multicolour, blue, yellow, red, green, and purple. Gonadal quality assessment indicators are colour, firmness, and gonadal index. Gonads with good quality were shown by sea urchins from Laha beach (site 1) with a composition of 40% bright orange, 40% yellow/pale yellow, and 20% brown, very firm of 80% and not firm of 20%, and a gonadal index value of 7.57 %. In contrast, gonads with poor quality were shown by sea urchins from Erie beach (site 4) with a composition of 80% brown and 20% grey, a very firm of 60% and firm of 40%, and a gonadal index value of 3.08%. This different quality is thought to be the result of microplastic accumulation in the sea urchin organs, which causes the satiated delusion. This study shows that sea urchins in the waters of Outer Ambon Bay have been affected by the dangers of microplastics by decreasing the quality of the gonads produced. Therefore, it is necessary to prevent the waste problem in the waters of Ambon Bay and to cultivate long-term sea urchins.